Association between fundamental motor skills and executive function in preschool children: A cross-sectional study - Han, Xiaowei; Zhao, Meiling; Kong, Zhe; Xie, Jun (Frontiers in Psychology, 2022)
Objective: The main purpose of this study was to explore the association between early fundamental motor skills (FMS) and executive function (EF) in preschool children. Methods: A total of 394 young children (4.07 ± 0.76 years) were evaluated. The FMS and EF were evaluated using the Test of Gross Motor Development-2 (TGMD-2) and the NIH Toolbox Cognition Battery (NTCB), respectively. Results: Total FMS score was moderately and positively correlated with total EF score (r = 0.33, p < 0.001) and was a significant predictor of total EF score (β = 0.37, p < 0.001). Specifically, locomotor skills were significant predictors of inhibition control (β = 0.21, p < 0.001), working memory (β = 0.18, p < 0.01), and cognitive flexibility (β = 0.24, p < 0.001), while object control skills were only significant predictors of inhibition control (β = 0.17, p < 0.01). Conclusion: FMS were significantly and positively correlated with EF and were significant predictors of EF. Early childhood policymakers, preschool teachers, and researchers should take these connections seriously and implement appropriate complex motor intervention programs in future teaching to stimulate the development of both motor and higher-order cognitive skills in preschool children.